Language networks in anophthalmia: maintained hierarchy of processing in ‘visual’ cortex - Watkins, Kate E.; Cowey, Alan; Alexander, Iona; Filippini, Nicola; Kennedy, James M.; Smith, Stephen M.; Ragge, Nicola; Bridge, Holly (Brain (London, England : 1878), 2012)
Imaging studies in blind subjects have consistently shown that sensory and cognitive tasks evoke activity in the occipital cortex, which is normally visual. The precise areas involved and degree of activation are dependent upon the cause and age of onset of blindness. Here, we investigated the cortical language network at rest and during an auditory covert naming task in five bilaterally anophthalmic subjects, who have never received visual input. When listening to auditory definitions and covertly retrieving words, these subjects activated lateral occipital cortex bilaterally in addition to the language areas activated in sighted controls. This activity was significantly greater than that present in a control condition of listening to reversed speech. The lateral occipital cortex was also recruited into a left-lateralized resting-state network that usually comprises anterior and posterior language areas. Levels of activation to the auditory naming and reversed speech conditions did not differ in the calcarine (striate) cortex. This primary "visual" cortex was not recruited to the left-lateralized resting-state network and showed high interhemispheric correlation of activity at rest, as is typically seen in unimodal cortical areas. In contrast, the interhemispheric correlation of resting activity in extrastriate areas was reduced in anophthalmia to the level of cortical areas that are heteromodal, such as the inferior frontal gyrus. Previous imaging studies in the congenitally blind show that primary visual cortex is activated in higher-order tasks, such as language and memory to a greater extent than during more basic sensory processing, resulting in a reversal of the normal hierarchy of functional organization across "visual" areas. Our data do not support such a pattern of organization in anophthalmia. Instead, the patterns of activity during task and the functional connectivity at rest are consistent with the known hierarchy of processing in these areas normally seen for vision. The differences in cortical organization between bilateral anophthalmia and other forms of congenital blindness are considered to be due to the total absence of stimulation in "visual" cortex by light or retinal activity in the former condition, and suggests development of subcortical auditory input to the geniculo-striate pathway.